#PolarizedFeeds: Three Experiments on Polarization, Framing, and Social Media. (July 2021) - Banks, Antoine; Calvo, Ernesto; Karol, David; Telhami, Shibley
Does exposure to social media polarize users or simply sort out like-minded voters based on their preexisting beliefs? In this paper, we conduct three survey experiments to assess the direct and unconditioned effect of exposure to tweets on perceived ideological polarization of candidates and parties. We show that subjects treated with negative tweets see greater ideological distance between presidential nominees and between their parties. We also demonstrate that polarization increases with processing time. We demonstrate a social media effect on perceived polarization beyond that due to the self-selection of like-minded users into different media communities. We explain our results as the result of social media frames that increase contrast effects between voters and candidates.